Characteristics of Mathematics Books for Junior High School Grade 7 Merdeka Curriculum Praxeological Analysis of Cuboids Volume - Azzumar, Fuji; Herman, Tatang; Turmudi, Turmudi (Universitas Sebelas Maret, 2023)
This study aims to analyze the characteristics of the mathematics books used in the Merdeka Curriculum in grade 7 junior high school, with a focus on praxeological analysis in the context of volume cuboids. The research method used is content analysis with a four-component approach to praxeology. The four components are types of tasks, techniques, technology and the last is theory. The results of the research show that the design of textbooks does not provide a type of task that facilitates students to acquire theory independently. This, guides researchers to create alternative designs for the task that provides meaningful learning experience in reference to cuboids volume material